2012
DOI: 10.1166/jnn.2012.5702
|View full text |Cite
|
Sign up to set email alerts
|

Growth of E18 Rat Hippocampal Neuronal Cells on Nanostructured Surfaces for Enhanced Electrical Stimulation and Recording

Abstract: We have prepared gold nanowire arrays inside nanoporous alumina templates with the goal towards neuronal interfacing and electrical recording from neurons. We have investigated biofunctionalization of such gold nanowire arrays (GNWs) and gold nanofilm (GNF) platforms to understand its impact on neuronal attachment and growth. Poly-D-Lysine (PDL) was coated on the nano-templates surfaces for adhesion of neurons which also enhanced the neuronal growth. Optical microscopy and scanning electron microscopy images r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition, to facilitate neuronal adhesion to substrates, factors such as laminin and poly-D-lysine (PDL) are used in in vitro cell culture preparations and are vital for attachment and growth on various surfaces. Prior studies have demonstrated that PDL forms a strong interface between the underlying nano-surfaces and neuronal cells, leading to improved adhesion and interconnectivity of neuronal networks [52]. Similarly, proteins such as laminin have been shown to successfully adsorb to gold surfaces via physiosorption and form permissive growth areas for neuronal cells [53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to facilitate neuronal adhesion to substrates, factors such as laminin and poly-D-lysine (PDL) are used in in vitro cell culture preparations and are vital for attachment and growth on various surfaces. Prior studies have demonstrated that PDL forms a strong interface between the underlying nano-surfaces and neuronal cells, leading to improved adhesion and interconnectivity of neuronal networks [52]. Similarly, proteins such as laminin have been shown to successfully adsorb to gold surfaces via physiosorption and form permissive growth areas for neuronal cells [53].…”
Section: Discussionmentioning
confidence: 99%